1997
DOI: 10.1111/j.1365-2044.1997.074-az0074.x
|View full text |Cite
|
Sign up to set email alerts
|

Can ASA grade or Goldman's cardiac risk index predict peri‐operative mortality? A study of 16 227 patients

Abstract: SummaryThis trial was designed to study the correlation between peri-operative mortality in patients undergoing elective surgery and the physical status classification of the American Society of Anesthesiologists, the Goldman multifactorial cardiac risk index or the two indices combined. All patients scheduled for elective surgery over a 5-year period were evaluated pre-operatively and were scored according to both indices. Of 16 227 patients studied, 215 died within 4 weeks of operation. Both indices correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(74 citation statements)
references
References 14 publications
3
67
0
4
Order By: Relevance
“…[21][22][23] Hamlet et al reported a relationship between preoperative health status and the time to postoperative mortality, and late functional outcome in hip fracture patients. 24 Preoperative health status was assessed by the ASA classification.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Hamlet et al reported a relationship between preoperative health status and the time to postoperative mortality, and late functional outcome in hip fracture patients. 24 Preoperative health status was assessed by the ASA classification.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lee Goldman as author [6,16,[19][20][21][22][23][24][25] and coauthor [5,15,17,18,[26][27][28][29][30][31], as well as studies of other authors that used Goldman's CRI [7][8][9][10][11][12][13], found statistical significance of the incidence of all types of perioperative cardiac complications between the four stratification subgroups of patients undergoing noncardiac surgery. The same studies proved that all 9 Goldman's risk factors were independent predictors of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they established highly significant differences between four stratification groups in the incidence of perioperative minor, major and fatal cardiac complications [6]. Using Goldman's cardiac risk index in the following 30 years, many studies confirmed and validated its clinical significance, and therefore, the index is today widely used in perioperative medicine [7][8][9][10][11][12][13]. One study compared four scoring systems for risk evaluation in noncardiac surgery, among which Goldman's cardiac Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Even simple subjective measures such as the ASA (American Society of Anesthesiologists) score stratify patients by surgical risk [10]. A combination of risk factors such as age, co-morbidity, presenting pathology, proposed surgery and physiological measurements have been used in several studies [11][12][13].…”
mentioning
confidence: 99%